Code of Ethics for HR Practitioners in the Public Sector under the Civil Service of Thailand - Joungtrakul, Jamnean (HRD Journal, 2013)
The purpose of this study was to develop a code of ethics for HR practitioners in the public sector under the Civil Service of Thailand. Two data collection methods, document review and focused group interviews were applied in this study. A purposive sampling technique was used to select participants for focused group interviewees and a qualitative data analysis method was employed in analysing data. As a result of this study a code of ethics for HR practitioners in public sector under the Civil Service of Thailand was developed. The code of ethics was presented in a model of “TRUSTS” comprising of: (1) T-Treating others with integrity, legality, and non-discrimination in human resource management; (2) R-reliable proficiency and continuous learning in human resource professionals; (3) U-upholding confidentiality and information sharing; (4) S-stably being role models in human resource ethics code; (5)T- thoughtfulness in handling conflicts of interest in human resource management; and (6) S- support others to have a balance of work and life. A set of expected behaviours for the code of ethics for each HR function was also developed, supplemented by a code of ethics handbook for use in implementation. A three-step approach to implementation was recommended using: (1) awareness; (2) commitment; and (3) engagement mechanisms. Keywords : Code of ethics; HR practitioners, civil service, integrity, legality, non-discrimination, proficiency, learning, confidentiality, information sharing, role model, conflict of interests, balance of work and life